Improving Health and Welfare in KAGUM (Malaysian Teachers' Cooperative) through VCO (Virgin CoconutOil) - Suryani, Suryani; Rafnelly Rafki; Monik Kasman; Rinda Lestari; Ermawati; Sari Puspita (KPN Kopertis X, 2025)
The Malaysian Teachers' Cooperative (KAGUM) in Malacca is a cooperative with 679 active members out of a total of 4,387 teachers in the region. In addition to playing a role in improving welfare through savings and loan programs and productive businesses, KAGUM also has the potential to develop health-based businesses. Virgin Coconut Oil (VCO) is known to have extensive health benefits, including antioxidants, antimicrobials, and immunity-boosting. This community service was carried out by a team from Indonesia in collaboration with KAGUM (Malaysian Teachers' Cooperative) in Malacca which is an International PKM activity. This Community Service was carried out by the KPN Kopertis Region X Cooperative with 44 members who departed from PKM. Of the 26 private universities. aims to provide education about the health benefits of VCO as well as training in making VCO products, online marketing so that it has high economic value. Methods of activities include scientific presentations, demonstrations of making household-scale VCOs, and interactive discussions related to VCO business opportunities, as well as how to market online in a cooperative environment. As a result, participants gained an increase in knowledge by 85% (from pre-test and post-test) and showed high interest in developing VCO business as a cooperative's flagship product. This activity is expected to strengthen the health of members and increase cooperative income through diversification of businesses based on tropical natural resources